The Effect of Patient Sex on the Incidence of Early Adverse Events in a Population of Elderly Patients. Issue 4 (July 2014) - Conti, D.; Ballo, P.; Boccalini, R.; Boccherini, A.; Cantini, S.; Venni, A.; Pezzati, S.; Gori, S.; Franconi, F.; Zuppiroli, A.; Pedullà, A.
Patient sex is known to influence the response to general and regional anaesthesia and recovery after surgery. However, most studies come from analyses carried out on middle-aged patients. As most of the patients admitted to the post-anaesthesia recovery room in our institution are elderly, we took the opportunity to investigate the association between sex and incidence of early adverse events in this older population of patients after major surgery. Consecutive patients undergoing general, orthopaedic, urological and gynaecological surgery, admitted to the recovery room of our institution over a 15-month period, were retrospectively studied. The following adverse events were considered in the analysis: shivering, postoperative nausea and vomiting, hypotension and hypertensive responses, new arrhythmias requiring treatment, acute respiratory failure and desaturation. A total of 1347 patients (mean age 73.3±15.1 years, 61.4% women) were included. Women showed a higher incidence of shivering (relative difference +48%, P =0.0003), postoperative nausea and vomiting (+91%, P <0.0001), hypotension (+32%, P =0.044) and desaturation (+60%, P =0.0030) than men. The incidence of hypertensive response, arrhythmias and acute respiratory failure were not statistically significantly different. The findings of this exploratory study suggest that women have a higher risk of early postoperative adverse events even in a more elderly population.